Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kompetensi Guru di SD Se-Kecamatan Kandis Kabupaten Ogan Ilir - Reni Kurniawati; Bukman Lian; Heri Setiyo Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is to find out and analyze the existence or absence of influence between the principal's leadership and work motivation together on the competence of elementary school teachers in Kandis District, Ogan Ilir Regency. This research is all elementary schools in Kandis District, Ogan Ilir Regency totaling 12 State Elementary Schools. This research lasted for five months, starting from the research planning preparation stage in early January 2024 to May 2024. Based on the type of data used, this study uses a quantitative approach. The population in this study is all teachers at State Elementary Schools in Kandis District, Ogan Ilir Regency for the 2023/2024 school year, consisting of 101 teaching staff. Based on the calculation using the Slovin formula, the sample in this study amounted to 81 teachers. The data collection of this research was carried out using questionnaires. The data analysis technique in this study uses inferential statistics, namely simple linear regression test and multiple linear regression test. The result of this study is that the leadership of the principal and work motivation together have a significant effect on the competence of teachers at SD Negeri Sekecamatan Kandis Ogan Ilir. The influence of all independent variables on teacher competence is 92% and the remaining 8% is influenced by other variables that are not studied in this study. Keywords: Leadership, Principal, Motivation, Competence, Elementary School Teacher